Expect the unexpected – Implications for next phase of COVID-19 response. Issue 2 (June 2021) - Clifford, Sarah; Cevik, Muge; Campbell, Robyn; O'Shea, Dàire; Sutherland, Rebecca
Summary: A case report of a 66 year old male patient with COVID 19 who presented late in the clinical course and subsequently developed respiratory failure requiring intubation, after initially experiencing diarrhoea.